Immunization Program Implementation as the Effort to Achieve Universal Child Immunization (UCI) - Fikri (Journal of Public Health and Pharmacy)
Immunization is the government's promise to achieve Sustainable Development Goals (SDGs) specially to reduce the number of child deaths, where Universal Child Immunization (UCI) is an indicator of the success of complete basic immunization in infants to increase immunity to a disease. UCI coverage in Central Sulawesi Province was not achieved in 2021 by 77.1% causing uneven UCI achievement in all puskesmas. One of the reasons for the failure of UCI is the management process. So, this study aims to analyze the immunization management process in an effort to achieve UCI. This research is a qualitative study with a phenomenological approach. This research was conducted at the Kawatuna Health Center. The data collection method was through in-depth interviews with 3 informants, consisting of the head of the puskesmas, the holder of the immunization program and the implementing midwife. The results showed that the availability of resources was not optimal because the qualifications of officers were not in accordance with existing standards, training was only carried out by immunization program holders and inadequate facilities and infrastructure such as KMS supplies, facilities where immunization was carried out outside the building and the absence of official official vehicles. The implementation of the immunization program has also not gone well, namely the absence of counseling before immunization is held in the field, the lack of enthusiasm of the community in the implementation of immunization as well as ignorance and lack of cross-sectoral involvement in the implementation of immunization and the absence of direct monitoring by the Head of the Health Center for immunization activities outside the building. Based on these results, it is hoped that the Provincial Health Office of Central Sulawesi will conduct training for all immunization officers and provide official vehicle procurement. The Head of the Puskesmas is expected to carry out direct monitoring of immunization services outside the building and not only to monitor the results of the officer's report. For the Puskesmas, it is expected to hold counseling about the importance of immunization for target parents before Posyandu services. Cross-sectors are expected to support the implementation of immunization, play an active role and cooperate in the implementation of immunization.